2020
DOI: 10.1111/tid.13478
|View full text |Cite
|
Sign up to set email alerts
|

Nocardia prophylaxis, treatment, and outcomes of infection in lung transplant recipients: A matched case‐control study

Abstract: Background Lung transplant recipients are at heightened risk for nocardiosis compared to other solid organ transplant recipients, with incidence rates as high as 9% and up to 30% associated mortality. No controlled studies assessing risk factors for nocardiosis in this high‐risk population have been reported. Methods Patients undergoing lung transplantation at a single center between 2012 and 2018 and diagnosed with nocardiosis post‐transplant were matched 1:2 to uninfected control subjects on the basis of age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 21 publications
3
19
0
Order By: Relevance
“…Out of four lung transplant recipients who received TMP‐SMX DS weekly, two experienced recurrent infection while on prophylaxis suggesting such dosing was not protective. This is similar to findings in a recent study evaluating primary prophylaxis in lung transplant recipients found TMP‐SMX as compared to either no or inconsistent use of TMP‐SMX, which was found to be protective against Nocardia infection with an odds ratio of 0.038 24 . However, other studies in mixed SOT populations have shown inconsistent results 5,6,13 .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Out of four lung transplant recipients who received TMP‐SMX DS weekly, two experienced recurrent infection while on prophylaxis suggesting such dosing was not protective. This is similar to findings in a recent study evaluating primary prophylaxis in lung transplant recipients found TMP‐SMX as compared to either no or inconsistent use of TMP‐SMX, which was found to be protective against Nocardia infection with an odds ratio of 0.038 24 . However, other studies in mixed SOT populations have shown inconsistent results 5,6,13 .…”
Section: Discussionsupporting
confidence: 88%
“…found to be protective against Nocardia infection with an odds ratio of 0.038. 24 However, other studies in mixed SOT populations have shown inconsistent results. 5,6,13 As lung transplant recipients appear to be at higher risk for primary and recurrent nocardiosis, this group may derive more benefit from consistently dosed primary or secondary prophylaxis.…”
Section: Discussionmentioning
confidence: 97%
“…The only two TMP/SMX-resistant strains were MDR, according to the criteria of Magiorakos et al [ 34 ]. In recent work by Goodlet et al [ 35 ], previous TMP/SMX prophylaxis in lung transplant patients has been found to be an independent protective factor for nocardiosis; nonetheless, one of our patients who received TMP/SMX prophylaxis developed an infection sustained by a resistant strain.…”
Section: Discussionmentioning
confidence: 49%
“…In patients with lung transplantation, infections caused by Nocardia species, such as N. farcinica, N. nova, and N. asteroids, have been reported (3)(4)(5)(6)(7). However, to our knowledge, there have been no reports of N. elegans infection in lung transplant recipients.…”
Section: Introductionmentioning
confidence: 95%